The Effect of Work Environment, Work Conflict, and Workload Towards Occupational Stress among Private Universities Lecturers in Surakarta City - Bingar Hernowo; Anton Respati Pamungkas (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of environment, conflict, and workload towards Occupational Stress among private Universities Lecturers in Surakarta City. Sampling was conducted with convenience method.  There were 100 lecturers from private universities in Surakarta participated in this study. Data was analyzed using the Smart PLS3 application. The study results show that work environment influenced the occupational stress of lecturers. The work environment influenced the lecturers’ workload. Work conflict affected the workload. Work conflict affected occupational stress of lecturers. Workload affected occupational stress of lecturers. Conclusion In overall, hypothesis test results show that all determined models contributed to a significant effect. The highest variable for occupational stress during the Covid 19 pandemic was the work environment. Based on this result, universities should improve the facilities to support the safety and convenience of the work environment. The work conflict variable had a higher influence value on lecturer workload therefore the role of leader in tertiary management was highly important in anticipating prolonged conflicts in the work environment to prevent  interference on the quality of performance and quality of universities.